Tanggap Kebal dan Tampilan Produksi Ayam Pedaging yang Diberi Ekstrak Buah Mengkudu (IMMUME RESPONSE AND PRODUCTION PERFORMANCE OF BROILERS GIVEN NONI FRUIT EXTRACTS) - Hamzah, Razak Achmad; Wiryanti, Ida; Astuti, Dewi Apri; Satrija, Fadjar (Jurnal Veteriner; Vol 13 No 1 (2012), 2012)
Noni fruit (Morinda citrifolia) has been used extensively as a drug, which is advertised with a varietyof benefits, such as can increase endurance, improve productivity. Those statements have not been provedscientifically. The results of this study, are expected to provide some information to the public regardingthe true benefits of Morinda citrifolia. The aims of this research were to study the effect of Noni (Morindacitrifolia) fruit extract given to broilers to their antibody titers and the counts of lymphocytes, basophils,eosinophils, monocytes, heterophils, and leukocytes. Production performance of these chickens was alsostudied. One hundred and sixty Cobb’s strain of broilers were used in this researh and were divided intofour groups of treatments which were divided into four experiment units which each comprised of tenchickens. Mengkudu fruit extract was given for 14 consecutive days orally using doses 0.0 g, 0.1 g , 0.5 g, and1.0 g per kilogram of body weight (kbw). The chickens utilized as control (0.0 g /gbw) were given only thesame plain water which was used to extract the fruits. The blood sampling were collected at the 3rd, 5th, 14th,and 21st days of the research. The study showed mengkudu fruit extract given at dose of 0.5 g/kbw was ableto elevate immune response (antibody) significantly if given in seven succesive days, and maintain toperform as an antiallergic when the extract given at dose 0.1, 0.5, dan 1.0 g/kww for 5 consecutive days. Butthe effect on the production performance had never been observed at all level of the dose and duration ofobservation.
Keywords: Morinda citrifolia, broiler, antibody, lymphocytes